2011
DOI: 10.1136/thx.2010.143180
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-gamma release assays for tuberculosis screening of healthcare workers: a systematic review

Abstract: Healthcare workers (HCWs) are at increased risk of exposure to tuberculosis (TB). Traditionally, screening for latent TB infection (LTBI) is done using the tuberculin skin test (TST). Interferon-gamma release assays (IGRAs) are now increasingly being used for diagnosis of LTBI, but their role in HCW screening is unclear. A systematic review was conducted of all IGRA studies in HCWs to summarise their performance in cross-sectional and serial testing settings. By searching four electronic databases and other so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
202
5
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(239 citation statements)
references
References 71 publications
29
202
5
3
Order By: Relevance
“…As highlighted in a recent systematic review, the reversion of IGRA serial testing results is common among HCWs and more frequently observed than conversion (37). Our data suggest that this observation is explained by regression toward the means, a ubiquitous and inevitable, though often missed, statistical phenomenon that occurs whenever repeated measurements on the same subject are observed with random error, i.e., nonsystematic variation around a true mean (1).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…As highlighted in a recent systematic review, the reversion of IGRA serial testing results is common among HCWs and more frequently observed than conversion (37). Our data suggest that this observation is explained by regression toward the means, a ubiquitous and inevitable, though often missed, statistical phenomenon that occurs whenever repeated measurements on the same subject are observed with random error, i.e., nonsystematic variation around a true mean (1).…”
Section: Discussionmentioning
confidence: 68%
“…Recently, systematic reviews have shown that IGRAs have excellent specificity for the diagnosis of LTBI even in Bacillus Calmette-Guérin (BCG)-vaccinated populations (8,23). Furthermore, they correlate with occupational risk factors of TB exposure in low-incidence settings (37).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dentre as vantagens, os IGRAs parecem não ser influenciados pela vacinação prévia com BCG 26 , necessidade de apenas uma visita (sem retorno para a leitura, como no TT), resultados em 24 horas, eliminação de erros de aplicação e interpretação de leitura do TT, uso de pequeno volume de sangue e ausência do efeito booster, por não expor o próprio paciente a um antígeno 27 . Zwerling et al 28 concluiram que o uso de IGRAs, ao invés do TT para uma triagem unica, pode resultar emuma prevalênciamenor deTT positivoe uma quantidade menor de profissionais de saúde que requeiram tratamento de TL, particularmente em locais onde a incidência de TB é baixa. Por outro lado, o uso de IGRAs ainda não está validado para o uso de rotina no Brasil 2 .…”
Section: Discussionunclassified
“…These assays quantify the in vitro release of IFN-γ from T-cells stimulated with Mycobacterium tuberculosis (M. tuberculosis) antigens. The innovation, together with their prevailing employment, facilitates the early identification of atrisk individuals allowing for early intervention treatment for latent TB infection, thereby preventing the spread of TB in health care settings and communities where the TB patients reside [1,2].…”
Section: Introductionmentioning
confidence: 99%